2017
DOI: 10.1016/j.neuropharm.2017.01.027
|View full text |Cite|
|
Sign up to set email alerts
|

A selective CB2R agonist (JWH133) restores neuronal circuit after Germinal Matrix Hemorrhage in the preterm via CX3CR1+ microglia

Abstract: Microglia play dual roles after germinal matrix hemorrhage, and the neurotrophic phenotype maybe neuroprotective. However, the phenotype transformation and the way by which neuron-microglia dialogue remain unclear. We raise the hypothesis that a cannabinoid receptor2 agonist (JWH133) accelerates the CX3CR1 microglia secreting neurotrophic factors and restores damaged neuronal circuit. Here, we report a novel function of JWH133 in transforming the microglia CX3CR1 positive that secrete brain-derived neurotrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…The latter morphology is thought to be related to classical (M1) activation though microglia have a ramified cell shape with a small soma when in the homeostatic (M0) state. In line with the morphological data, studies showed that eCB administration increased the expression of CD200R in vitro in a mixed neuron/microglia culture (93) and CX3CR1 in a stroke model (113), both of which are thought to be associated with alternative (M2) and homeostatic (M0) states (133). Although it remains uncertain whether the increase in homeostatic microglia is merely an epiphenomenon of terminated neuroinflammation, eCB signaling may directly shift microglial morphology toward not only the neuroprotective (M2) phenotype but also the homeostatic (M0) phenotype, in which microglia are known to have important physiological functions, which include synaptic pruning, synaptic plasticity modulation, and neuronal trophic support (46).…”
Section: Perspectives and Future Issuessupporting
confidence: 66%
See 2 more Smart Citations
“…The latter morphology is thought to be related to classical (M1) activation though microglia have a ramified cell shape with a small soma when in the homeostatic (M0) state. In line with the morphological data, studies showed that eCB administration increased the expression of CD200R in vitro in a mixed neuron/microglia culture (93) and CX3CR1 in a stroke model (113), both of which are thought to be associated with alternative (M2) and homeostatic (M0) states (133). Although it remains uncertain whether the increase in homeostatic microglia is merely an epiphenomenon of terminated neuroinflammation, eCB signaling may directly shift microglial morphology toward not only the neuroprotective (M2) phenotype but also the homeostatic (M0) phenotype, in which microglia are known to have important physiological functions, which include synaptic pruning, synaptic plasticity modulation, and neuronal trophic support (46).…”
Section: Perspectives and Future Issuessupporting
confidence: 66%
“…This study demonstrated that the eCB system modulates both M1 and M2 marker expression in a timedependent manner in the brain injury model. In a later study, they examined the effects of long-term treatment with JWH133 in the disease model and found that microglia adopted a ramified cell shape and showed increased expression of CX3CR1, the fractalkine receptor (113). CX3CR1 is not regarded as an M2 marker; however, upon binding to the neuron derived ligand, CX3CR1 suppresses microglial activation and enables microglia to return to the homeostatic state.…”
Section: Microglial Polarization By Ecb In Cerebral Hemorrhage and Stmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, inhibition of inflammatory response is critically important at the early stage after GMH. Microglia are resident immune cells in the central nervous system (CNS) (Tang J et al, 2017). Following GMH, microglia are activated immediately and release proinflammatory cytokines, such as tumor necrosis factor-α (TNF-α) and interleukin-6 (IL-6), leading to secondary brain injury (Brouwer et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In two separate studies, CB1R antagonists SR141716A and AM251 were shown to have beneficial effects in attenuating neuronal damage caused by cerebral ischemia [ 418 , 419 ]. Interestingly, CB2R agonists have also been shown to mitigate inflammatory states and promote neurogenesis in post stroke and post intracerebral hemorrhage [ 420 , 421 ]. The possibility of employing a dual CB1R antagonist/CB2R agonist strategy to attain effective coverage in attenuating the severity of ischemic injury, could be a viable therapeutic strategy based on the available pre-clinical data [ 422 , 423 ].…”
Section: Biological Role Of the Cannabinoid Receptorsmentioning
confidence: 99%